A study of reproductive efficiency of White Fulani cows as observed in old dairy of Teaching and Research Farm, University of Ibadan - Kehinde, F.E. (1976)
The reproductive performance of White Fulani cows was investigated. Records at Shika and Ibadan University farm from 1971 to 1975 were analysed. Discussions and data on average age at first calving, calving interval and rate, pregnancy index, abortion, neonatal mortality, dystocia, congenital malformation and average lactation yield included.